2018
DOI: 10.3389/feduc.2018.00100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Explaining on Learning and Transfer of Critical Thinking Skills

Abstract: Critical thinking is considered to be an important competence for students and graduates of higher education. Yet, it is largely unclear which teaching methods are most effective in supporting the acquisition of critical thinking skills, especially regarding one important aspect of critical thinking: avoiding biased reasoning. The present study examined whether creating desirable difficulties in instruction by prompting students to generate explanations of a problem-solution to themselves (i.e., self-explainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 54 publications
(71 reference statements)
4
31
2
1
Order By: Relevance
“…Moreover, several tasks were taken from previous studies that were conducted in similar contexts (i.e. within an existing CT-course with first-year or second-year students of a university of applied sciences; Heijltjes et al, 2014a;Heijltjes et al, 2014bHeijltjes et al, , 2015 and even within the same study domain (Van Peppen et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, several tasks were taken from previous studies that were conducted in similar contexts (i.e. within an existing CT-course with first-year or second-year students of a university of applied sciences; Heijltjes et al, 2014a;Heijltjes et al, 2014bHeijltjes et al, , 2015 and even within the same study domain (Van Peppen et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The power of Experiment 1under a fixed alpha level of 0.05 and with a correlation between measures of 0.3 (e.g. Van Peppen et al, 2018) is estimated at .24 for detecting a small interaction effect (h 2 p = .01), .96 for a medium interaction effect (h 2 p = .06), and > .99 for a large interaction effect (h 2 p = .14). Thus, the power of our experiment should be sufficient to pick up medium-sized interaction effects, which is in line with the moderate overall positive effect of interleaved practice of previous studies as indicated in a recent meta-analysis (g = 0.42; Brunmair & Richter, 2019).…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, critical thinking requires a high level of abstract and logical thinking and a commitment or habit of thinking to meet the standards and principles of good critical thinking. Such skills are defined as reflective and reasoned ways of thinking that are focused on deciding what the individuals believe and can do (van Peppen et al, 2018). Delphi's consensus involving various experts managed to discuss about CTS as the purpose of assessment and learning.…”
Section: Introductionmentioning
confidence: 99%